High-rate cathode CrSSe based on anion reactions for lithium-ion batteries. Issue 48 (7th December 2020) - Yang, Si-Yu; Shi, Ding-Ren; Wang, Tian; Yue, Xin-Yang; Zheng, Lei; Zhang, Qing-Hua; Gu, Lin; Yang, Xiao-Qing; Shadike, Zulipiya; Li, Hong; Fu, Zheng-Wen
Abstract : CrSSe is a novel layered electrode material based on anionic reactions of S and Se. And a new type of lithium-ion battery is fabricated when paired with soft carbon, in which Li3 N film was in situ generated on the electrode surface as the sole lithium source. Abstract : Studies of transition metal dichalcogenides (TMDs) can be traced back to the 1970s but they have been abandoned for a while due to the fire hazard of lithium metal batteries. Herein, a new layered material, CrSSe, is reported, whose intercalative capacity can achieve 190 mA h g −1 with charges all compensated by anionic S and Se. Fascinating performances of half-cells are also presented, with a capacity retention rate of 81.5% upon 1000 cycles at 20C and a high output of 101.7 mA h g −1 even at 200C. In addition, an ideal way to build a type of full battery without lithium anodes for CrSSe is also displayed; a Li3 N film was synthesized on the electrode surface as a lithium source. Overall, the discovery of CrSSe enriches the chemistry of TMDs and the application in full batteries opens up opportunities for enabling lithium-free cathodes to be widely utilized in practical applications.